Analysis of reaction kinetics for torrefaction of pelletized agricultural biomass with dry flue gas. (December 2020) - Onsree, Thossaporn; Tippayawong, Nakorn
Abstract: Biomass torrefaction is a simple and appropriate thermo-chemical treatment/conversion process for upgrading agricultural residues to a high-quality fuel, which could be used as an alternative energy resource to replace fossil fuels. In this paper, reaction kinetics for torrefaction of pelletized agro-residues biomass under dry flue gas conditions were investigated. The two-step mechanism model was used to describe the biomass torrefaction decomposition, and with the experimental data, the kinetic parameters of this model were analyzed. The torrefaction reactions were found to occur in a narrow period of reaction time, and the kinetic parameters were affected by dry flue gas conditions. The model predictions can imitate the thermo-chemical degradation well, and the predicted torrefied solid was shown to contain not only chars but also some intermediate and unreacted fractions. This work provides further insights for understanding torrefaction kinetics of agricultural biomass pellets which are important in designing and operating industrial biomass conversion equipment and apparatus.